A Coupled System of Caputo–Hadamard Fractional Hybrid Differential Equations with Three-Point Boundary Conditions. (11th July 2022) - Arab, Meraa; Awadalla, Muath
Abstract : This article presents a study of the existence and uniqueness of solutions for a system of hybrid fractional differential equations involving fractional derivatives of the Caputo-Hadamard type with three-point hybrid boundary conditions. In addition to this, the "Hyres–Ulam" stability of the solutions for this type of equation is verified, and finally a numerical example was presented to support our theoretical results.